Atomic-Scale Modelling and its Application to Catalytic Materials Science. Issue 3 (1st July 2015) - Sarwar, Misbah; Cooper, Crispin; Briquet, Ludovic; Ukpong, Aniekan; Perry, Christopher; Jones, Glenn
Computational methods are a burgeoning science within industry. In particular, recent advances have seen first-principles atomic-scale modelling leave the realm of the academic theory lab and enter mainstream industrial research. Herein we present an overview, focusing on catalytic applications in fuel cells, emission control and process catalysis and looking at some real industrial examples being undertaken within the Johnson Matthey Technology Centre. We proceed to discuss some underpinning research projects and give a perspective on where developments will come in the short to mid-term.